2021
DOI: 10.18805/ijar.b-4813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Dietary Protein Levels on Physio-metabolic Response during Stunting of Milkfish, Chanos chanos (Forsskal, 1775) Reared under Pond Conditions

Abstract: Background: Stunting is a process of suppressing growth from unfavourable conditions. The protein supplementation during stunting gives scope to maintain the nutrient reserves of fish and its quality. Methods: A feeding trial was conducted for eight months to study the effect of three hetero-nitrogenous diets with 25% (control), 30% (T1) and 35% (T2) crude protein (CP) levels on growth and physio-metabolic responses of Chanos chanos fingerlings during stunting. Milk fish fingerlings with a mean body weight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Surjobala et al (2021) worked on the effect of graded protein levels on the growth, survival and body composition of Osteobrama belangeri using semi purified diet and suggests that the optimum dietary protein level of 25% gives the best performance in terms of growth, survival, feed utilization and whole-body carcass composition of O. belangeri. Whereas, Prasad et al (2022) studied effect of different dietary protein levels on physio-metabolic response during stunting of milkfish, Chanos chanos reared under pond conditions and concluded that that the dietary protein level has a significant role in producing quality milkfish fingerlings during stunting. Squid meal protein, which makes up a large part of the fat-insoluble portion, has been shown to improve egg quality (Fernandez-Palacios et al 1995).…”
Section: Proteinmentioning
confidence: 99%
“…Surjobala et al (2021) worked on the effect of graded protein levels on the growth, survival and body composition of Osteobrama belangeri using semi purified diet and suggests that the optimum dietary protein level of 25% gives the best performance in terms of growth, survival, feed utilization and whole-body carcass composition of O. belangeri. Whereas, Prasad et al (2022) studied effect of different dietary protein levels on physio-metabolic response during stunting of milkfish, Chanos chanos reared under pond conditions and concluded that that the dietary protein level has a significant role in producing quality milkfish fingerlings during stunting. Squid meal protein, which makes up a large part of the fat-insoluble portion, has been shown to improve egg quality (Fernandez-Palacios et al 1995).…”
Section: Proteinmentioning
confidence: 99%